2021
DOI: 10.1002/gch2.202100019
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Quantitative Instruments for Understanding Breastfeeding Dynamics

Abstract: More than two decades ago, breastfeeding was recognized as the most effective international preventive health intervention, with the potential to prevent 13% of deaths among children younger than 5 years of age worldwide. [3] Studies have shown that infants who do not receive human milk are at higher risk for a number of medical issues, including necrotizing enterocolitis, [4,5] gastrointestinal and upper respiratory tract illness, [6,7] and urinary tract infections. [8] The World Health Organization suggests … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…In this paper, we focus on suckling vacuum as a starting point as prior research has shown that infant's intraoral vacuum is essential to effective milk extraction [28]. An analysis of NNS vacuum signals can provide infant oral measurement information such as mean oral vacuum, suckling frequency, burst duration, sucks per burst, maximum vacuum, and signal shape, details important in understanding infant suckling behavior [29,23]. These measurements provide key information on an infant's suckling ability and can be used to determine infant suckling irregularities.…”
mentioning
confidence: 99%
“…In this paper, we focus on suckling vacuum as a starting point as prior research has shown that infant's intraoral vacuum is essential to effective milk extraction [28]. An analysis of NNS vacuum signals can provide infant oral measurement information such as mean oral vacuum, suckling frequency, burst duration, sucks per burst, maximum vacuum, and signal shape, details important in understanding infant suckling behavior [29,23]. These measurements provide key information on an infant's suckling ability and can be used to determine infant suckling irregularities.…”
mentioning
confidence: 99%